School Curriculum and Parentsâ Support on Kindergarten Studentsâ Caring Attitude - Puspitasari, Dewi Natalia; Mardila, Dini; Kirana, Kartika (Universitas Muhammadiyah Surakarta, 2018)
Being care is an important attitude that children learn. Nowadays, itbecomes more important when children grow in the environment with workingparents, gadgets, television, and individual society. Therefore, ExperimentalMangunan Kindergarten has four values, and one of the values is âbeing careâ. Thisresearch was held to find how school curriculum and parents support studentsâ caringattitude. This is a qualitative research with grounded theory method, which is held inExperimental Mangunan Kindergarten in Yogyakarta. There are two studentsâ casesin this research. The respondents of the interview were taken purposively. They werethe school principal, two teachers, and the studentsâ parents. Data collections wereheld by observation, interview, and reading teachersâ journals. The result was thatthe two students who have not yet caring to others when first entered MangunanSchool, were grow to have caring attitude after eight months. These findings showthat school curriculum, teachersâ and parentsâ relation toward kindergarten studentsare important part to grow studentsâ caring attitude.